Karakteristik operasi pompa kalor tipe kompresi uap dengan fluida kerja R114 - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT Exsperiments to inverstigate the operating characteristics of a heat pump system operating on RI 14 have been done. The effects of the operating conditions of heat pump system including temperature and mass flow of heat source fluid